Exploring Advances in Vehicle Safety through the Integration of Artificial Intelligence Technology: A Systematic Review - Sarika A. Patil, Ganesh E. Kondhalkar, Atul A. Patil, Lalit N. Patil, Vijaykumar K. Javanjal, Kuldeep A. Mahajan, Nikhil M. Shinde (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Following the adoption of artificial intelligence (AI) technologies, there have been implementations that aim to apply intelligence in their respective fields. Various approaches to building a safe automobile transport system have been suggested in the past. This is a novel literary framework for mapping of artificial intelligence (AI) in vehicle safety system. This paper offers a comprehensive analysis of vehicle safety aspects, focusing on how new technologies had been employed in development of vehicle safety over the past few years. The existing literature has been extensively examined. Principal and secondary "search strings" were recognized. A search was performed on five databases, followed by screening and analysis. Thirty primary studies conducted between 2009 and 2023 were chosen from the total literature reviewed. From the comprehensive reading of this paper, the reader’s interest will be enriched with: 1) Finding out the current research trends in automotive safety using artificial intelligence techniques, 2) Recognizing the upcoming challenges in vehicle safety and report whether the AI can solve the challenges?, 3) Which algorithms are preferred for artificial intelligence in vehicles? 4) Present research work going on in the field of vehicle safety and road map towards the safe drive.